"Turning Japanese": Deconstructive Criticism of White Women, the Western Imagination, and Popular Music. (27th July 2016) - Oh, David C.
Abstract: Singers Katy Perry and Avril Lavigne are among the most recent White women performers to appropriate Japanese femininity. In Perry's November 2013 performance of "Unconditionally, " she used Orientalist imagery of premodern Japan, and in Lavigne's 2014 single "Hello Kitty, " she used techno-Orientalist imagery of Harajuku street fashion, kawaii, and Japanese-as-cyborg. I argue that like White women performers, who performed Japanese femininity in the turn of the 20th century, Perry and Lavigne caricatured Japanese femininity as a hybrid costume to advance their own subjectivities. Yet, I also show through deconstructive criticism that their spectacular use of juxtaposition and excess creates "obtuse meanings" in which subversive meanings escape and opportunistically challenge the dominant meaning of the texts.